5th February: 5th Sunday after Epiphany - Knights, Chris H. ca. 196? (The expository times, 2017)
The article critiques the chapters Matthew 5. verses 13-20 and Isaiah 58. verses 1-12 from the bible focusing on seeking the light of God while fighting for justice.